2018
DOI: 10.1002/cnm.3153
|View full text |Cite
|
Sign up to set email alerts
|

Computational aeroacoustics to identify sound sources in the generation of sibilant /s/

Abstract: A sibilant fricative /s/ is generated when the turbulent jet in the narrow channel between the tongue blade and the hard palate is deflected downwards through the space between the upper and lower incisors and then impinges the space between the lower incisors and the lower lip. The flow eddies in that region become a source of direct aerodynamic sound, which is also diffracted by the speech articulators and radiated outwards. The numerical simulation of these phenomena is complex. The spectrum of an /s/ typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 64 publications
(111 reference statements)
1
28
1
Order By: Relevance
“…As regards the sizes of the vortices, a n , they deserve some closer inspection. In Pont et al, the CFD simulations revealed that for frequencies below approximately 2.3 kHz, the pressure energy spectrum was apparently constant in average. Beyond that frequency, the energy smoothly decreased until 12 kHz, where the Kolmogorov turbulent cascade started.…”
Section: Problem Statementmentioning
confidence: 96%
See 4 more Smart Citations
“…As regards the sizes of the vortices, a n , they deserve some closer inspection. In Pont et al, the CFD simulations revealed that for frequencies below approximately 2.3 kHz, the pressure energy spectrum was apparently constant in average. Beyond that frequency, the energy smoothly decreased until 12 kHz, where the Kolmogorov turbulent cascade started.…”
Section: Problem Statementmentioning
confidence: 96%
“…Given that we need to capture frequencies up to 12 kHz for the correct reproduction of a sibilant sound like /s/, and that we have Mach numbers MscriptO()103 (though locally values of 0.2 can be reached), very fine computational meshes are required to solve the problem. To get a better idea of the computational demands, we notice that generating 10.8 ms of an /s/ took 30 hours in a cluster of 256 processors with a mesh of 45 million tetrahedral elements in Pont et al The 10.8 ms suffice for spectral analysis but not if one wants to generate an audio file from the computed acoustic pressure, or if one wished to produce a more complex sound like syllable /sa/. Therefore, our goal is to try to find an approximation to Lighthill tensor (3), which essentially results in a similar acoustic output (ie, the sibilant sound) to one obtained from CFD.…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations